Green synthesis of CuO nanoparticles using Curcuma longa L. extract: composite dielectric and mechanical properties - Orhan, Ramazan (Walter de Gruyter Gmbh, 2025)
Green synthesis, one of the methods of obtaining metallic nanoparticles using plants, is preferred because it is simpler, eco-friendly, and economical and has the ability to reduce metallic ions using phytochemicals in its structure. This study investigates the green synthesis of CuO nanoparticles using turmeric (Curcuma longa L.) extract, the structural, chemical, and morphological properties of the synthesized CuO nanoparticles, and the effects on the dielectric and mechanical properties of the nano-CuO-doped epoxy nanocomposites. The total phenolic content of turmeric extract was determined using the Folin-Ciocalteu method. The structural and morphological properties of the synthesized CuO nanoparticles were characterized by UV-Vis, FTIR, XRD, FE-SEM, EDX, and TEM. The charge distribution of the nanoparticles was determined using a Zetasizer. It was determined that the shape of the synthesized CuO nanoparticles was spherical and the average particle size was 62 nm. Nanofilms and nanocomposite materials were prepared by adding the synthesized CuO nanoparticles to epoxy resin, and their effects on the dielectric and mechanical properties were investigated. An increase in the epsilon ' and epsilon '' values of the doped-nanocomposite films was observed compared with those of the pure epoxy film. It was determined that nanocomposites also improved the tensile strength and hardness values.
Keywords: CuO nanoparticles; Curcuma longa L.; epoxy resin; green synthesis; nanocomposite